2022
DOI: 10.7759/cureus.22043
|View full text |Cite
|
Sign up to set email alerts
|

Re-Hospitalization in First Six Months After Live Related Renal Transplantation: Risk Factors, Burden, Causes and Outcomes

Abstract: The aim of our study was to evaluate the incidence, causes, risk factors, outcomes, and cost of hospital readmission after live related renal transplantation (LRRT). MethodsWe conducted a cross-sectional study and followed patients' re-admissions for six months whose LRRT was done in our center between September 2019 and June 2020. ResultsWe recruited 53 patients, 40 (75.5%) were male. The mean age was 36.9 ± 11.9 years. Donor gender was similar, and their mean age was 31.6 ± 9.2 years. The mean length of hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Regarding the association between sociodemographic factors and readmission after renal transplantation, the results suggest that there is no significant association between the gender, age, and BMI of the patients and their likelihood of readmission after renal transplantation. These findings are consistent with some previous studies, which also found no significant association between gender and readmission after renal transplantation [17]. It is because the factors that influence readmission rates are more related to medical complications and other individual patient characteristics rather than gender.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the association between sociodemographic factors and readmission after renal transplantation, the results suggest that there is no significant association between the gender, age, and BMI of the patients and their likelihood of readmission after renal transplantation. These findings are consistent with some previous studies, which also found no significant association between gender and readmission after renal transplantation [17]. It is because the factors that influence readmission rates are more related to medical complications and other individual patient characteristics rather than gender.…”
Section: Discussionsupporting
confidence: 92%
“…Infectious complications, especially UTIs are one of the most important causes for hospital readmission after transplantation. In this context, a recent research in 2022 has shed light on the considerable burden imposed by infectious complications as the leading cause of readmission after KTX with 49% of all cases, and with 39% of UTIs [ 18 ]. These complications not only contribute to the overall patient's well being but also pose an important cost burden on the healthcare system.…”
Section: Prevalence and Impact Of Urinary Tract Infections On Healthc...mentioning
confidence: 99%